The EU's Eastern void: mapping non-cooperation between the European Union and the Russia-led Eurasian Economic Union - Blidaru, Mădălin (Technium Social Sciences Journal, 2022)
Regions have distinctive features in the global governance and the interregional cooperation, while integration processes reduce the probability of conflict. By focusing on the cooperation between the European Union and the Eurasian Economic Union, a system of indicators measuring the levels of integration of the neighbours of the European Union with the EU is proposed in this paper. From a perspective based on regional arrangements, the author aims to assess the levels of integration and cooperation in the EU's neighbourhood from West to the East and North to the South, focusing on the particularities of cooperation with the Eurasian Economic Union. A system based on 18 indicators based on open data across four dimensions (economic cooperation, political cooperation, human development, institutional cooperation) is used for the measurement at the given time. Using the comparative approach, it identifies the possible channels for improving the cooperation between the European Union and the Eurasian Economic Union. The results are presented as rankings of the integration scoring for the overall system and for dimensions, followed by a discussion on the Eurasian case.